2007
DOI: 10.1111/j.1439-0485.2007.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

A benthic mucilage event in North‐Western Mediterranean Sea and its possible relationships with the summer 2003 European heatwave: short term effects on littoral rocky assemblages

Abstract: In this contribution we document an anomalous mucilage growth which occurred in June 2003 along the rocky cliffs of the Portofino Promontory (Ligurian Sea, NW Mediterranean Sea), and we describe its dynamics and its negative effects on many benthic taxa. The zooxanthellate scleractinian Cladocora caespitosa underwent ‘bleaching’ and about 40% of biomass of the erect algae was detached by mucilage ‘lianas’ created and strengthened by bottom currents. The 2003 event differed from any other previously occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 44 publications
3
65
0
Order By: Relevance
“…The Ligurian Sea has suffered in recent decades major changes in the structure of benthic communities and fish stocks due to anthropization of the coastline, pollution, fisheries and phenomena linked to global warming (Schiaparelli et al . ; Puce et al . ; Parravicini et al .…”
Section: Discussionmentioning
confidence: 99%
“…The Ligurian Sea has suffered in recent decades major changes in the structure of benthic communities and fish stocks due to anthropization of the coastline, pollution, fisheries and phenomena linked to global warming (Schiaparelli et al . ; Puce et al . ; Parravicini et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ilan et al (1994) reported it dubiously from a depth of 830 m off the Israeli Mediterranean coast. On the contrary, Bianchi and Morri (1983) and Schiaparelli et al (2007) reported it as shallow as 3 m, in the Aegean, and 12 m, in the Ligurian Sea, respectively. In all these records, the species came from rocks dispersed amidst sand or mud, or from rocky reefs.…”
Section: Introductionmentioning
confidence: 90%
“…In the western Mediterranean Sea, besides two large-scale episodes in September 1999 (Cerrano et al 2000;Perez et al 2000) and July 2003 (Schiaparelli et al 2007), mass mortalities occurred also in 2002, 2006(Garrabou et al 2009), always impacting shallow-water communities (above 40 m depth) where the seasonal temperature oscillations are wider.…”
Section: Introductionmentioning
confidence: 99%